Neologizmy słowotwórcze w słowniku Obserwatorium Językowego Uniwersytetu Warszawskiego (na materiale haseł opracowanych do lutego 2022 roku). Część 3: Derywaty adiektywne i werbalne - Rybarski, Mateusz (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2024)
This article constitutes the third part of a cycle devoted to 1 117 Polish derivational neologisms in Obserwatorium Językowe Uniwersytetu Warszawskiego (Language Observatory of the University of Warsaw). Its aim is to present and analyse 92 adjectival and 119 verbal derivatives in the Polish language divided into groups of derivational neologisms created by the use of the same formative technique and affix. The study concludes that the largest class among the described new adjectival derivatives in contemporary Polish language consists of suffixal structures and that the largest class of new verbal derivatives includes structures with inflectional formative. As for the morphemes used to create them, the suffixes -owy and -owa-/-uj- turned out to be the most productive.